2021
DOI: 10.1155/2021/8847307
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Is a Prognostic Biomarker and Associated with Immune Infiltration in Kidney Renal Clear Cell Carcinoma: Implication for COVID-19

Abstract: Background. KIRC is one of the most common cancers with a poor prognosis. ACE2 was involved in tumor angiogenesis and progression in many malignancies. The role of ACE2 in KIRC is still ambiguous. Methods. Various bioinformatics analysis tools were investigated to evaluate the prognostic value of ACE2 and its association with immune infiltration in KIRC. Results. ACE2 was shown to be downregulated in KIRC at the mRNA and protein level. Low expression of ACE2 protein in KIRC patients was observed in subgroup an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…However, many KIRC patients still develop drug resistance and progressive diseases, increasing the risk of a poor prognosis [4]. e 5-year overall survival (OS) of stage-IV KIRC patients is less than 10% [5,6]. A recent study revealed that the immune cell response is significantly associated with the prognosis in KIRC [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, many KIRC patients still develop drug resistance and progressive diseases, increasing the risk of a poor prognosis [4]. e 5-year overall survival (OS) of stage-IV KIRC patients is less than 10% [5,6]. A recent study revealed that the immune cell response is significantly associated with the prognosis in KIRC [7].…”
Section: Introductionmentioning
confidence: 99%
“…The ACE inhibitor hypertension drug relieves vasoconstriction by inhibiting ACE expression and increasing ACE2 expression, which restricts the conversion of angiotensin I to angiotensin II [ 45 , 46 , 47 ]. Furthermore, ACE2 expression is inversely related to tumor angiogenesis and progression in many cancers [ 48 , 49 , 50 , 51 , 52 ]. Therefore, future study on KC in vivo should closely monitor RAS regulation and cancer prognosis, which may be caused by KC binding to the ACE2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…We performed gene-disease (GD) analyses to predict signi cant association between DEGs and different diseases. The experiment's outcome showed the top 10 diseases involved in hub DEGs, including Myocardial Infarction,Tumor Angiogenesis,Chronic Kidney Failure,Migraine Disorders,Colorectal Cancer, Colorectal Neoplasms, Squamous cell carcinoma of the head and neck, Cerebrovascular Disorders, Coronary heart disease,Cerebrovascular accident.In our study, we identi ed several diseases associated with both COVID-19 and HF.SARS-COV-2 could lead to a hypercoagulable state and a poor prognosis in patients with acute myocardial infarction (MI), and MI was also an important cause of HF (70).ACE2 was involved in tumor angiogenesis and progression in many malignancies (71).One study showed that SARS-COV-2 uses ACE2 to enter serine protease TMPRSS2 to activate S protein (72). From this point of view,tumor angiogenesis,COVID-19 and HF were related through ACE system.…”
Section: Discussionmentioning
confidence: 99%